Electrical fuse lets chips heal themselves. - Geppert, L.
The electronic system of the future will monitor itself, change the functions it performs, and repair its damaged circuits-all without external intervention. Such is the dream of autonomic computing. Although the dream is not yet reality, engineers and scientists at IBM Corp. have taken a big step with the development of an on-chip fuse that is electrically blown-or programmed, as the company prefers to call the process-by using a physical effect heretofore considered a serious reliability problem in semiconductor circuits. According to IBM, combining the new eFuse technology with already available on-chip built-in self-test and -repair circuitry will yield a chip capable of diagnosing its failures and then fixing them by blowing fuses to reroute its circuits.
Keywords: eFuse technology; Electric fuse; Electrically programmable fuses; Fault diagnosis; On chip fuse; Self healing circuit; Semiconductor circuit reliability